Could the human papillomavirus recombinant vaccine be a new valid approach in the management of ano-genital warts? - Sarro, A.; Airoldi, C.; Pedicini, A.; Di Tullio, E.; Pecere, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
In line with previous case-reports, the study conducted by Hoom Choi ascertained the effectiveness of the HPV vaccine as a promising approach in the therapeutic management of ano-genital warts. The uncertain length of time and the varying effectiveness of traditional treatments encourage a reduction in the use of them and the development of a therapeutic use of HPV-vaccination. While the efficacy, safety profile and effects of the HPV vaccination in preventing ano-genital warts is well-know, therapeutic HPV vaccination has not been evaluated in a Randomized Prospective Trial, to date, and has not received a formal approval and an off-label indication for the treatment of those lesions. For these reasons, RCTs or cohort studies are warranted.